Leiomyomatosis Peritonealis Disseminata (LPD) ten years after laparoscopic myomectomy associated with ascites and lymph nodes enlargement: a case report. (2016) - Nappi, Luigi; Sorrentino, Felice; Angioni, Stefano; Pontis, Alessandro; Barone, Ida; Greco, Pantaleo
Highlights: Leiomyomatosis peritonealis disseminata (LPD) is a rare pathology of unkown etiology. The relationship of LPD with myoma morcellation remains unclear. Ascites with lymph node enlargement can be present in LPD. Time of clinical presentation of LPD can be very long after laparoscopic myomectomy. Abstract: Introduction: We report a case of leiomyomatosis peritonealis disseminata (LPD) arising 10 years after a laparoscopic myomectomy that was associated with ascites and lymph nodes enlargement. Presentation of case: The patient presented with small uterine fibroids with a dominant posterior intramural fibroid measuring 9 cm in diameter and normal Doppler. Laparotomy revealed a uterus enlarged with fibroids, which was densely adhering to the urinary bladder, greater omentum, and sigmoid colon. Multiple tumors of different size were found attached to the peritoneum, omentum and bowel. The histopathologic examination was consistent with leiomyomatosis peritonealis disseminata. Discussion: Pieces of smooth muscle cell lost in the abdominal cavity during electrical morcellation after laparoscopic myomectomy may progress to leiomyomatosis peritonealis disseminata even after many years (ten in our case) and it can be associated with ascites and lymph nodes enlargement. Conclusion: This is the first case reported in literature of leiomyomatosis peritonealis disseminata with these particular features (time of clinical presentation, ascites, lymph nodes enlargement).